Karakteristik dan Upaya Pencegahan Penularan Pada Penderita Tuberkulosis Paru - Mila Triana Sari; Haflin Haflin; Dayana Rahmaniyah (Universitas Batanghari Jambi, 2020)
Pulmonary tuberculosis is still a global priority health problem because it is the leading cause of death in the world for infectious diseases. According to WHO, Indonesia ranks third in the world after India and China. Estimated cases of pulmonary tuberculosis in Indonesia in 2019, as many as 845,000 people, while the prevalence of patients with pulmonary tuberculosis is 142 per 100 thousand population, Jambi ranked 5th in Indonesia. Lung tuberculosis is highly contagious, and can have a devastating effect on family members who live in the same house as people with pulmonary tuberculosis, if prevention efforts are not made by those with pulmonary tuberculosis. The purpose of this study was to identify the characteristics and efforts to prevent transmission in patients with pulmonary tuberculosis. This research is a descriptive study, with a total sampling technique, conducted on 42 people with pulmonary TB in the work area of PKM Putri Ayu Jambi City. Use demographic and transmission prevention instruments. Data collection was carried out by guided interviews. The results showed. The highest age in patients with pulmonary tuberculosis is productive age (23.8%) with male sex (57.1%) the highest education is basic education (40.5%) and employment is IRT (31.0%). Whereas prevention of transmission for more than half (54.8%) is good. It is expected that patients with pulmonary tuberculosis can increase their knowledge related to the knowledge of pulmonary tuberculosis, how to treat and prevent pulmonary tuberculosis transmission and to be actively involved in the eradication of pulmonary tuberculosis, while the health center staff and cadres can conduct counseling about efforts to prevent transmission of pulmonary tuberculosis to increase public knowledge about lung tuberculosis eradication, while the health center staff and cadres can conduct counseling about efforts to prevent the transmission of pulmonary tuberculosis prevention of pulmonary tuberculosis, as well as periodically do homevisit to the place of residence of tubulosis patients to monitor the condition of pulmonary tuberculosis sufferers.